2023
DOI: 10.1002/celc.202201130
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Cycling Behaviour and Shape Changes of Zn Electrodes in Mildly Acidic Aqueous Electrolytes Containing Quaternary Ammonium Salts

Abstract: Secondary Zn–based batteries are a valid alternative to Li for stationary storage, but commercial devices are not yet available, chiefly owing to anode shape‐change and passivation issues. Mildly acidic aqueous solutions are actively studied, since they seem to limit unstable growth of Zn, with respect to the alkaline ones, customary for primary batteries. Additives can further improve the performance of mildly acidic electrolytes. In this work we focus on the impact of a series of quaternary ammonium salts (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 60 publications
(132 reference statements)
1
7
0
Order By: Relevance
“…[26,27] Likewise, several studies have demonstrated the beneficial effect of some QAC, with TBA showing the best results so far. [28,29] The mechanism through which these cationic substances affect the electrochemical process is clear and related to the adsorption on the surface of the electrode, creating a barrier that controls the reaction rate. An exhaustive study of QAC with different chemical structure was conducted by Bozzini et al, [29] showing that inhibition of the cathodic reaction is the main factor leading to the improvement in cycling stability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[26,27] Likewise, several studies have demonstrated the beneficial effect of some QAC, with TBA showing the best results so far. [28,29] The mechanism through which these cationic substances affect the electrochemical process is clear and related to the adsorption on the surface of the electrode, creating a barrier that controls the reaction rate. An exhaustive study of QAC with different chemical structure was conducted by Bozzini et al, [29] showing that inhibition of the cathodic reaction is the main factor leading to the improvement in cycling stability.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] The mechanism through which these cationic substances affect the electrochemical process is clear and related to the adsorption on the surface of the electrode, creating a barrier that controls the reaction rate. An exhaustive study of QAC with different chemical structure was conducted by Bozzini et al, [29] showing that inhibition of the cathodic reaction is the main factor leading to the improvement in cycling stability. The synergetic effect between a complexing agent as DMSO together with an adsorbing additive, allows cycling for almost 250 h in comparison with the 120 h achieved in the absence of additives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations